Korespondensi Prinsip Pendidikan Anak dalam Tanqih al-Qawl Syeikh Nawawi al-Bantani dengan Temuan Neurosains Modern - Yuniarti, Nita; Shoheh, Muhamad; Abdushomad, Muhammad Adib; Ilmiah, Wardatul (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2026)
The principle of Islamic education through manners and parental affection poses challenges in understanding the relevance of classical Islamic texts to children's brain development. This study aims to examine the child education in Chapter 31 of Kitab Tanqīḥ al-Qawl al-Ḥathīth fī Sharḥ Lubāb al-Ḥadīth by Sheikh Nawawi al-Bantani and to correlate them with contemporary neuroscience findings regarding executive functions, socio-emotional development, sensitive periods, and neuroplasticity. The research employs a qualitative literature-based approach, with primary data from Chapter 31 of Tanqih al-Qawl and secondary data from contemporary neuroscience literature. A descriptive-comparative analysis was conducted to map correspondences between classical educational principles and neurobiological mechanisms. The findings indicate that classical principles, prioritizing moral education, holistic care, staged learning, spiritual-social dimensions, and parental responsibility, align with the development of neural networks, the limbic system, executive functions, and reward circuits, highlighting opportunities for integrating classical Islamic education with neuroscience-based pedagogy.